Vos autem estis advena: John of Luxembourg and the Political Argument of Foreignness in Fourteenth-Century Bohemia - Birkel, Christa (Historical Studies on Central Europe, 2022)
While Count John ‘the Blind’ is celebrated as a national hero in Luxembourg, in 1939 the Czech historian J. Šusta famously coined his image as the ‘King Foreigner’ (král cizinec). In fact, due to the murder of the last male Přemyslid, Wenceslas III, for the first time in history, the Kingdom of Bohemia was forced to elevate to king a representative of a non-Bohemian dynasty. To what extent was the first Luxembourg on the Bohemian throne considered ‘foreign’ in fourteenth-century Bohemia? What factors did his contemporaries use to define a potential otherness? The paper shows the phases of the rule of John of Luxembourg where the aspect of ‘foreignness’ determined public discourse, and the goals various groups of actors intended to achieve by recourse to it.